Implementing intranasal povidone-iodine in the orthopedic trauma surgery setting to prevent surgical site infections: a qualitative study of healthcare provider perspectives - AM Racila; Erin C. Balkenende; Loreen A. Herwaldt; Michael C. Willey; Linda D. Boyken; Jean G. Pottinger; Brennan S. Ayres; Kimberly C. Dukes; Melissa A. Ward; Marin L. Schweizer (Antimicrobial Resistance and Infection Control)
Abstract Background Surgical site infections (SSIs) are associated with morbidity, mortality, and increased costs. Staphylococcus aureus is the most common cause of SSIs and approximately 30% of hemodialysis patients carry this organism in their nares. Unlike mupirocin, intranasal povidone-iodine (PVI) is applied only the day of surgery to prevent surgical site infections. Thus, intranasal PVI could be valuable in orthopedic trauma surgery settings where time to prepare a patient for surgery is limited. Methods We conducted a small phase IV post-marketing study from 2020 to 2021 in an academically affiliated hospital wherein staff administered intranasal PVI pre- and post-operatively to consenting patients undergoing orthopedic fixation procedures for traumatic fractures. Before implementing the PVI intervention, we conducted a human factors task analysis to determine the optimal time and hospital location to perform PVI decolonization for patients receiving these orthopedic fixation procedures. After the post-marketing study was completed, we conducted qualitative interviews with healthcare staff to determine barriers and facilitators that could affect staff members’ likelihood of administering PVI to patients. We aligned our inductive interview findings with strategies defined in Powell and colleagues’ Expert Recommendations for Implementing Change (ERIC) framework to facilitate generalizability and standardized reporting of implementation strategies. Results Our human factors task analysis identified the Day of Surgery Admissions (DOSA) as the appropriate context for PVI administration within surgical workflow, as there was downtime during this period and direct patient-provider communication could occur. Two DOSA nurses, one postoperative nurse, and one orthopedic trauma surgeon agreed to be interviewed. Facilitators of intranasal PVI administration included emphasizing the non-invasiveness of PVI nasal swabs to patients and emphasizing intranasal PVI efficacy to staff and patients. While the nurse participants felt that having PVI orders with other medication orders in the EMR helped them identify patients enrolled in the study and who required PVI, entering these orders increased the surgeon’s workflow and presented a time barrier. Conclusions Macro- and micro-level contextual factors should be considered when tailoring implementation to healthcare settings. Our findings reinforce prior work demonstrating the value of incorporating human factors engineering methodologies into infection control and prevention implementation approaches.